ADOPSI NILAI-NILAI BUDAYA LOKAL DALAM KEPEMIMPINAN KEPALA SEKOLAH - Novi Fitriyanti; Rambat Nur Sasongko (UNIVERSITAS BENGKULU, 2020)
This study described what local cultural values are adopted in the leadership of principal at SMA Negeri 1 Bengkulu Tengah. This study used qualitative-descriptive method. In this paper, the subject of research was the principal. The data collected by using interview, observation and documentation. The results obtained indicate that the adoption of local cultural values in the leadership of principal has been implemented in appropriate with the principal's situation, condition and understanding of local cultural values.